Receptors determine the cellular localization of a γ‐tubulin complex and thereby the site of microtubule formation - Knop, Michael; Schiebel, Elmar (The EMBO journal, 1998)
The yeast microtubule organizing centre (MTOC), known as the spindle pole body (SPB), organizes the nuclear and cytoplasmic microtubules which are functionally and spatially distinct. Microtubule organization requires the yeast γ‐tubulin complex (Tub4p complex) which binds to the nuclear side of the SPB at the N‐terminal domain of Spc110p. Here, we describe the identification of the essential SPB component Spc72p whose N‐terminal domain interacts with the Tub4p complex on the cytoplasmic side of the SPB. We further report that this Tub4p complex‐binding domain of Spc72p is essential and that temperature‐sensitive alleles of SPC72 or overexpression of a binding domain‐deleted variant of SPC72 (ΔN‐SPC72) impair cytoplasmic microtubule formation. Consequently, polynucleated and anucleated cells accumulated in these cultures. In contrast, overexpression of the entire SPC72 results in more cytoplasmic microtubules compared with wild‐type. Finally, exchange of the Tub4p complex‐binding domains of Spc110p and Spc72p established that the Spc110p domain, when attached to ΔN‐Spc72p, was functional at the cytoplasmic site of the SPB, while the corresponding domain of Spc72p fused to ΔN‐Spc110p led to a dominant‐negative effect. These results suggest that different components of MTOCs act as receptors for γ‐tubulin complexes and that they are essential for the function of MTOCs.
Gesehen am 31.08.2017